2024
DOI: 10.1038/s44161-024-00462-8
|View full text |Cite
|
Sign up to set email alerts
|

Stroke and myocardial infarction induce neutrophil extracellular trap release disrupting lymphoid organ structure and immunoglobulin secretion

Ali A. Tuz,
Susmita Ghosh,
Laura Karsch
et al.

Abstract: Post-injury dysfunction of humoral immunity accounts for infections and poor outcomes in cardiovascular diseases. Among immunoglobulins (Ig), IgA, the most abundant mucosal antibody, is produced by plasma B cells in intestinal Peyer’s patches (PP) and lamina propria. Here we show that patients with stroke and myocardial ischemia (MI) had strongly reduced IgA blood levels. This was phenocopied in experimental mouse models where decreased plasma and fecal IgA were accompanied by rapid loss of IgA-producing plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 48 publications
(55 reference statements)
1
1
0
Order By: Relevance
“…In this present work, we show that DNase-fragmented NETs, but not intact NETs, directly potentiate T cell activation. In line with these results, a report showed that DNase treatment can prevent the reduction of T cell accumulation in lymphoid organs of ischemically injured mice [80].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In this present work, we show that DNase-fragmented NETs, but not intact NETs, directly potentiate T cell activation. In line with these results, a report showed that DNase treatment can prevent the reduction of T cell accumulation in lymphoid organs of ischemically injured mice [80].…”
Section: Discussionsupporting
confidence: 58%
“…In this present work, we show that DNase-fragmented NETs, but not intact NETs, directly potentiate T cell activation. In line with these results, a report showed that DNase treatment can prevent the reduction of T cell accumulation in lymphoid organs of ischemically injured mice [80]. Furthermore, DNase treatment or intratracheal administration of DNase-fragmented NETs were found to induce the activation of naive CD4 T cells adoptively transferred into lung allograft recipients, as well as to stimulate intragraft effector T cell accumulation [13].…”
Section: Discussionmentioning
confidence: 80%